Performance in digital transformation: Focus group insights - Geada, N.; Alturas, B. (World Journal of Information Systems, 2024)
This study leads into the world of digital transformation, specifically focusing on the dynamics of performance. Through a meticulously conducted focus group involving five diverse health professionals, this exploration aims to unravel transformation strategies and their impact on organizational performance. The focus group, conducted via videoconference in a relaxed environment, provided a platform for participants to freely express their opinions. The ensuing discussion, recorded and transcribed for qualitative analysis, centered on participants perceptions of digital transformation's influence on healthcare organizations. Thematic categories and recurring patterns were identified using content analysis software. With participants representing various backgrounds and perspectives, including neurology, rehabilitation, podology, neurophysiology, and hospital administration, the study embraces a comprehensive approach. The inclusion of both public and private healthcare sector representatives enriches the typology of thinking and mindset analysis. This abstract offers a snapshot of a focused inquiry into performance dynamics amid digital transformation, offering valuable insights for practitioners and researchers alike.